Seeds, browse, and tooth wear: a sheep perspective. Issue 16 (14th July 2016) - Ramdarshan, Anusha; Blondel, Cécile; Brunetière, Noël; Francisco, Arthur; Gautier, Denis; Surault, Jérôme; Merceron, Gildas
Abstract: While grazing as a selective factor towards hypsodont dentition on mammals has gained a lot of attention, the importance of fruits and seeds as fallback resources for many browsing ungulates has caught much less attention. Controlled‐food experiments, by reducing the dietary range, allow for a direct quantification of the effect of each type of items separately on enamel abrasion. We present the results of a dental microwear texture analysis on 40 ewes clustered into four different controlled diets: clover alone, and then three diets composed of clover together with either barley, corn, or chestnuts. Among the seed‐eating groups, only the barley one shows higher complexity than the seed‐free group. Canonical discriminant analysis is successful at correctly classifying the majority of clover‐ and seed‐fed ewes. Although this study focuses on diets which all fall within a single dietary category (browse), the groups show variations in dental microwear textures in relation with the presence and the type of seeds. More than a matter of seed size and hardness, a high amount of kernels ingested per day is found to be correlated with high complexity on enamel molar facets. This highlights the high variability of the physical properties of the foods falling under the browsing umbrella. Abstract : We here provide a unique dual dataset combining controlled food and dental microwear textures on a set of 40 domestic sheep. This study explores the variations in dental microwear textures among the guild of browsing ungulates feeding on leaves, fruits, and seeds. More than an experiment to explore the cause of toothwear, this study will be key work for paleoecologists to track the feeding ecology of earliest ruminants.